PENGARUH MOL REBUNG BAMBU TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PRE NURSERY - Abdullah Samosir; Gusniwati . (Bioplantae, 2014)
This study aimed to determine the effect of local microorganisms from fermented bamboo shoots (LM) on the growth of oil palm seedlings in pre nursery. This research used completely randomized design consisting of 6 levels  of treatment: Urea 2.0 g / L of water, 50.0 ml , 100.0, 150.0, 200.0 and 250.0 ml of LM from fermented bamboo shoots. The growth parameter  plant height, leaf area, root dry weight, and shoot dry weight   was measured every week. The results showed LM from bamboo shoots  fermented significantly affected oil palm seedling growth at 50 ml /L of water.  The highest  in seedling height, diameter of seedling, number of leaves, leaf area, dry weight, root dry weight  was achieved at  50.0 ml/L water of LM. Keywords: Bamboos, local microorganism, fermented, pre-nursery